White Matter Hyperintensities as a Risk Factor for Ischemic Stroke in Patients With Systemic Lupus Erythematosus - Sano, Eri; Arawaka, Shigeki (Frontiers in Neurology, 2021)
Objective: The occurrence of ischemic stroke in patients with systemic lupus erythematosus (SLE) can cause extended periods of reduced daily activities. However, the risk factors for ischemic stroke in SLE patients are not fully elucidated. Herein, we examined the effect of white matter hyperintensities (WMH) on the occurrence of ischemic stroke in SLE patients. Methods: We analyzed the relationship between WMH burden and ischemic stroke using follow-up brain magnetic resonance imaging (MRI) data of 79 patients with SLE. Of these patients, 16 developed stroke during the observation period. WMH on MRI were classified into periventricular hyperintensities and deep white matter hyperintensities (DWMH), while the lesion extent was graded using the Fazekas scale. Results: Kaplan–Meier curves showed that ischemic stroke events were significantly associated with age at initial brain MRI of ≥40 years (p = 0.015) and history of anti-phospholipid syndrome (p = 0.030). Additionally, ischemic stroke events were significantly associated with a one grade deterioration of periventricular hyperintensities (p = 0.003) and a one grade deterioration of DWMH (p = 0.002). Multivariate analysis using the logistic regression model showed that a one grade deterioration of DWMH was an independent risk factor for ischemic stroke (hazard ratio, 6.0; 95% confidence interval, 1.3–27.4). Conclusions: Although several factors affect the occurrence of ischemic stroke, SLE patients show increased risk of ischemic stroke via development of DWMH. An observation of DWMH deterioration on follow-up brain MRI may be useful for assessing the risk of ischemic stroke in SLE patients.